Implementation of Digitalization and Technology-Driven Waste Management Education - -, Suryatiningsih; Dewi Budiwati, Sari; Gartina Husein, Inne; Hadiyoso, Sugondo; Octaviany, Vany (PPM Universitas Telkom, 2026)
Waste management remains a major challenge in Lengkong Village, Bandung Regency, due to the limited capacity of existing waste processing facilities and low community participation in source level waste reduction. The current TPS 3R is unable to accommodate waste generated by 13 neighborhood units, resulting in uncontrolled accumulation that poses environmental and public health risks, while community-based waste management practices based on the 3R principles have not been optimally implemented. As an initial effort, the Mekar Arum Mewangi Waste Bank Unit (BSU MAMMA), established in February 2024, has encouraged household level waste sorting among residents of RW 11; however, its impact remains limited. Therefore, this community service program focuses on education on segregated waste management and deposit procedures, training in the development of waste management educational content, and the development of a digital application to support waste bank operations, aiming to improve data management, transaction recording, and reporting. The initiative is implemented in collaboration with the Coimbatore Institute of Technology, which contributes expertise in decentralized and technology-based waste management, and targets BSU MAMMA members and residents of RW 11 with potential expansion to other areas. Through this approach, the program is expected to foster a more participatory, effective, and sustainable waste management system, ultimately enhancing environmental quality and public health in Lengkong Village. Keywords : waste, sorting, waste management, application